Judicial reform in Ukraine as an important step on the way to the state’s membership in the European Union - Tetiana Kazik (Конституційно-правові академічні студії, 2023)
The purpose of the article is to analyze the current state of the judicial reform in Ukraine, to elicit problematic aspects in this area, and to identify trends in the further development of judicial reform. The methodological basis of the research article is a set of cognition methods, the application of which allowed to reveal the essence of the proposed problem. Since gaining independence, Ukraine has chosen to pursue European integration. Since then, the process of adapting national legislation to that of the European Union has begun. Therewith, the Visa Liberalization Action Plan should be recognized as one of the most effective incentives in terms of judicial reform. However, despite the numerous achievements in the field of judicial reform, the judicial reform in our country is still incomplete, which is a significant obstacle to Ukraine’s full membership in the European Union, in view of the violation of the Convention’s right to a fair trial. The level of access provided by national legislation must be sufficient to ensure the right to a trial in view of the rule of law in a democratic society. In order for access to be effective, a person must have a clear, practical opportunity to challenge actions that interfere with his or her rights. Effective access to justice for any individual and the proper administration of that justice indicate the success of judicial reform and the restoration of its confidence in national courts. The supremacy of law will not be possible without proper access to justice. Therefore, the judicial reform needs to be further implemented. To continue the judicial reform is one of the steps Ukraine must take to become a full member of the European Union. Priority areas for further reform of the judiciary should include strengthening the supremacy of law; combating corruption; eliminating shortcomings of the information and telecommunication system of electronic justice; raising the level of professional competence of judges by creating a professional development system that will include training, advanced training and exchange of experience with colleagues from other countries; introducing initiatives for such vulnerable groups of court users as victims and witnesses of war crimes, combatants and members of their families.